2018
DOI: 10.3122/jabfm.2018.04.170325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Medical Scribes in Primary Care on Productivity, Face-to-Face Time, and Patient Comfort

Abstract: Background: Medical scribes are a clinical innovation increasingly being used in primary care. The impact of scribes in primary care remain unclear. We aimed to examine the impact of medical scribes on productivity, time spent facing the patient during the visit, and patient comfort with scribes in primary care.Methods: We conducted a prospective observational pre-post study of 5 family and internal medicine-pediatrics physicians and their patients at an urban safety net health clinic. Medical scribes accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 24 publications
(34 reference statements)
5
50
1
Order By: Relevance
“…When scribes were present, physicians spent more time in the encounter looking at the patient as opposed to the computer, a finding that was marginally significant. This is consistent with other similar findings in the literature [16]. Patients noticed that that their physician was the professional using the computer more frequently in nonscribed encounters as compared to scribed encounters (93% vs 52.6%), but this factor too had little impact on patients’ perceptions of the encounter.…”
Section: Discussionsupporting
confidence: 92%
“…When scribes were present, physicians spent more time in the encounter looking at the patient as opposed to the computer, a finding that was marginally significant. This is consistent with other similar findings in the literature [16]. Patients noticed that that their physician was the professional using the computer more frequently in nonscribed encounters as compared to scribed encounters (93% vs 52.6%), but this factor too had little impact on patients’ perceptions of the encounter.…”
Section: Discussionsupporting
confidence: 92%
“…43 One recent study found that the use of scribes in primary care increased the number and intensity of patients seen per hour, increased patient-facing time, increased total physician-patient interaction time, decreased the time physicians spent interacting with a computer, and decreased the after-hours time spent in EMR documentation. 44 Other physician-driven changes in EMR processes may improve usability, patient safety, and physician job satisfaction, and decrease physician burnout. 45 In a paper entitled, "The Electronic Elephant in the Room," Philip Kroth and colleagues describe findings of structured interviews on the impact of EMR use on physicians (with the majority reporting EHR proficiency but also regularly spending "excessive" time at home documenting patient details in electronic charts).…”
Section: Clinical Significancementioning
confidence: 99%
“…Scribes have been shown to improve physician satisfaction, charting efficiency, productivity, and face-to-face communication with patients. [24][25][26][27][28] However, some have suggested that using scribes results in lost nuance and cognitive processing time, 29 and relatively little is known about the safety and accuracy of scriberelated documentation. 30 Moreover, scribes may not always be financially feasible.…”
Section: Background and Significancementioning
confidence: 99%